Adolescents with tracheostomies—Communications in cyberspace - Madan, Gitanjali; Stadler, Michael E.; Uhrich, Kim; Reilly, Cynthia; Drake, Amelia F. (International journal of pediatric otorhinolaryngology, 2011)
Social networking sites such as Facebook are popular avenues of social discourse among adolescents and young adults, allowing for communication through photographs, videos, and chat features. These websites are also emerging as portals for health-centered support groups, bringing together people with common medical conditions. Adolescents with tracheostomies represent a special and vulnerable patient population. Our aim was to determine whether this particular group of patients found Facebook to be a suitable environment in which to network with other users with tracheostomies. We used our institution's tracheostomy database to obtain a list of all patients between ages of 11–18. We identified 33 patients in this category, and completed a chart review to determine their medical diagnoses as well as age at trach placement. We determined that of these 33 patients, 24 had severe neurocognitive delays that would render them unable to participate in the study. We contacted the remaining nine subjects and obtained appropriate consent for their participation in the study. Of the nine subjects with tracheostomies who completed our survey, four were actively involved with the Facebook community. Two of the four subjects regularly connected with people that they had not met in person, and all four subjects shared the fact that they had a tracheostomy with the Facebook community. Three of the four subjects posted pictures of themselves with their trach sites visible. Finally, three of the four subjects stated that they met and communicated with other Facebook members with tracheostomies. Social networking sites such as Facebook appear to offer an appropriate avenue for adolescents with tracheostomies to network with other users with tracheostomies. Further studies are warranted to assess the reach and social impact of these networking sites as portals of health-centered support groups, however, social networking sites and the cyberspace community may be a promising source of support for adolescents with tracheotomies.